Experimental Study on Stress Corrosion Index Governing Time-Dependent Degradation of Rock Strength - Tae Young Ko; Sean Seungwon Lee (Applied Sciences, 2020)
Rock fractures in geological conditions are caused not only by applied stress, but also by stress corrosion. Stress corrosion is an environmentally activated chemical process, associated with the fluid-assisted crack growth. Crack growth due to stress corrosion is related to the time-dependent behaviours of rocks and is a crucial factor in determining the stability of underground structures over the long period of time. In this study, constant stress-rate tests including Brazilian tension and three-point flexural tests for the tensile strength, short-beam compression and single-shear tests for the in-plane shear strength, and a torsion test of rectangular section specimens and a circumferentially notched cylindrical specimen test for the out-of-plane shear strength were conducted at a different loading rate from 0.01 to 10 MPa/s using Coconino sandstone. The results show that the rock strength was proportional to the 1/(n+1)th power of the loading rate, where the parameter n indicates the stress corrosion index. The stress corrosion index (n) ranged from 34 to 38, with an average value of 36. The stress corrosion indices (n) were similar, irrespective of the loading configuration and specimen geometry. The stress corrosion index (n) can, therefore, be regarded as a material constant of rocks.